A Study on Nature of Violence Against Doctors in Tertiary Care Centers in Karnataka, India: A Cross-Sectional Study - Bharath Sekhar Nayanar; Nusrath Fareed; Hemanth Battur; Jaseela Praveena (Wolters Kluwer Medknow Publications, 2024)
Background: Over the previous decades, violence against physicians has risen. To comprehend the issue connected with it, we need to know the nature of violence and doctor's views on the current state of safety at their disposal. The purpose of the study was to assess the incidence and nature of violence against doctors in tertiary health care centers in Karnataka, India. Objectives: The objectives were to collect data from three tertiary care centers, evaluate the incidence of violence against doctors in tertiary care centers, and evaluate the nature of violence against doctors in tertiary care centers. Methods: From the list of all tertiary care centers in Dakshina Kannada, three tertiary care hospitals were randomly chosen. Approval of the Ethical Committee from the Institutional Ethics Committee (IEC) of KVG Dental College and permission from chosen hospitals were obtained. A pre-validated questionnaire was handed over to the available physicians and surgeons in these hospitals to be filled. The total number of participants in the study was 330. Results: Nearly half (48.02% of physicians) reported experiencing violence during working hours. The Department of Obstetrics and Gynaecology recorded 43.2% of instances, while surgery, medicine, and other departments reported 23.6%, 22.8%, and 10.4%, respectively. Conclusions: Violence against physicians continues to be a huge issue that must be addressed through decisive measures by the police and hospitals. This impacts the healthcare system in the nation and often cripples it owing to the loss of human resources and working hours.